Development of communication protocolbased on low voltage distribution automation system - M.M. , Ahmed; W.L., Soo (2007)
This paper presents the development of a customer side distribution automation system (DAS) for operating and controlling low voltage (LV) down stream of 415/240V by using the Tenaga Nasional Berhad (TNB) distribution system. Supervisory Control and Data Acquisition (SCADA) based remote Terminal Unit (RTU) along power line communication PLC) system are used for DAS development that practically imulates the down stream distribution system functions in an automated manner. It is the first DAS research work done on customer side substation for operating and controlling between the consumer side system and the substation. Most of the work is focused on building Human Machine Interface that provides a graphical operator interface function to monitor the system. The Human Machine Interface of SCADA system is developed using customized software and an RTU microprocessor and its software implements.